Trench-parallel fast axes of seismic anisotropy due to fluid-filled cracks insubducting slabs - Healy, David; Reddy, Steven; Timms, Nicholas Eric; Gray, Erin; Brovarone, A.V. (Elsevier Science BV, 2009)
Subducting slabs experience deformation and metamorphism as they descend into the upper mantle. Thepresence of hydrous minerals gained through the interaction with sea water at mid-ocean ridges, transformfaults or the outer rise ensures that dehydration reactions will be important at deeper levels. We describefield evidence for brittle hydrofracture in previously subducted rocks from the Western Alps, with a freeaqueous fluid phase produced by dehydration reactions in the host blueschists and serpentinites. Theprotracted history of dehydration reactions, ductile deformation, fluid flow and brittle vein formation inthese rocks implies that fluid-filled cracks are continuously produced within the dehydration window. Thepresence of abundant fluid-filled cracks at these depths has important implications for the seismic anisotropygenerated within slabs, which has largely been overlooked. The effects of fluid-filled crack damage on theelastic properties of a blueschist and serpentinite within the slab at depth have been modelled, and show asignificant rotation of the fast axes of P and S1 waves to be trench-parallel for receiving stations in the forearc,above the dehydrating portion of the slab. This model provides an alternative explanation for suprasubductionzone seismic anisotropy that does not require high-stress, high-water conditions, or trenchparallelflow in the supra-subduction zone mantle wedge.